Gradient-based and least-squares-based iterative algorithms for Hammerstein systems using the hierarchical identification principle - Ding, Feng; Liu, Xinggao; Chu, Jian (IET control theory & applications, 2013)
This study derives a least-squares-based iterative algorithm and a gradient-based iterative algorithm for Hammerstein systems using the decomposition-based hierarchical identification principle. The simulation results confirm that the proposed two algorithms can give satisfactory identification accuracies and the least-squares-based iterative algorithm has faster convergence rates than the gradient-based iterative algorithm.